Evaluasi Tingkat Pelayanan Jalan Studi Kasus: Jalan Gatot Subroto Jakarta - Ivan Kurniawan; Najid Najid (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2022)
Gatot Subroto is one of the primary roads in Jakarta with primary arterial type. Gatot Subroto road passes through two administrative cities, namely the administrative cities of South Jakarta and Central Jakarta. Currently, the Gatot Subroto Road has reduced it capacity due to overcrowding on the road, causing traffic jams. The research location in on the Gatot Subroto road Cawang to Grogol and Grogol to Cawang. In this study, we will discuss the level of service on Gatot Subroto road. The research method used the ministerial regulation number 14 of 2006, the ministerial regulation number 96 of 2015 and 1997 Indonesian Road Capacity Manual (MKJI). The research was conducted by using a traffic low survey method on Gatot Subroto road by noting the number of vehicles thast passing by, so that researchers can find out the capacity, free flow speed, volume, density, degree of saturation and level of service of these roads. From the results of data processing, the LOS value of each road directions is 1.70 and 1.41 so that it enters the service level category “category F”. Questionnaires were also distributed to 100 respondents. This questionnaire aims to obtain perception data in the form of the respondent’s speed and time when passing through the Gatot Subroto road in smooth, non-smooth and congested conditions. Then the results of direct analysis and questionnaires will be compared with the Regulation of the Minister of Transportation Regulation No.14 of 2006 and No.96 of 2015.Jalan Gatot Subroto merupakan salah satu jalan besar di Jakarta yang bertipe arteri primer. Jalan Gatot Subroto melewati dua kota adminstrasi yaitu kota administrasi Jakarta Selatan dan Jakarta pusat. Saat ini jalan Gatot Subroto kapasitasnya berkurang disebabkan karena kepadatan pada ruas jalan tersebut sehingga mengakibatkan kemacetan. Lokasi penelitian terdapat di ruas jalan Gatot Subroto Cawang arah Grogol dan Grogol arah Cawang. Pada penelitian ini, akan membahas mengenai tingkat pelayanan jalan di ruas Jalan Gatot Subroto. Acuan penelitian adalah Peraturan Menteri perhubungan no 14 tahun 2006, Peraturan Menteri perhubungan no 96 tahun 2015 dan Manual Kapasitas Jalan Indonesia (MKJI) 1997. Penelitian ini dilakukan dengan metode survey arus lalu lintas di jalan Gatot Subroto dengan mencatat jumlah kendaraan yang lewat, sehingga peneliti dapat mengketahui kapasitas, kecepatan arus bebas, volume, kepadatan, derajat kejenuhan dan tingkat pelayanan jalan dari ruas jalan tersebut. Dari hasil pengolahan data, diperoleh nilai LOS dari masing-masing arah jalan yaitu sebesar 1.70 dan 1.41 sehingga masuk ke kategori tingkat pelayanan “kategori F”. Dilakukan juga penyebaran kuesioner kepada 100 responden. Kuesioner ini bertujuan untuk mendapatkan data presepsi berupa kecepatan dan waktu responden saat melewati jalan Gatot Subroto dalam kondisi lancar, tidak lancar dan macet. Kemudian hasil observasi langsung dan kuesioner akan dibandingkan dengan Peraturan Menteri Perhubungan no 14 tahun 2006 dan no 96 tahun 2015.